Construction of an Escherichia coli strain unable to synthesize putrescine, spermidine, or cadaverine: characterization of two genes controlling lysine decarboxylase. - Tabor, H (1980)
We have previously described a polyamine-deficient strain of Escherichia coli that contained deletions in speA (arginine decarboxylase), speB (agmatine ureohydrolase), speC (ornithine decarboxylase), and speD (adenosylmethionine decarboxylase). Although this strain completely lacked putrescine and spermidine, it was still able to grow at a slow rate indefinitely on amine-deficient media. However, these cells contained some cadaverine (1,5-diaminopentane). To rule out the possibility that the presence of cadaverine permitted the growth of this strain, we isolated a mutant (cadA) that is deficient in cadaverine biosynthesis, namely, a mutant lacking lysine decarboxylase, and transduced this cadA gene into the delta (speA-speB) delta speC delta D strain. The resultant strain had essentially no cadaverine but showed the same phenotypic characteristics as the parent. Thus, these results confirm our previous findings that the polyamines are not essential for the growth of E. coli or for the replication of bacteriophages T4 and T7. We have mapped the cadA gene at 92 min; the gene order is mel cadA groE ampA purA. A regulatory gene for lysine decarboxylase (cadR) was also obtained and mapped at 46 min; the gene order is his cdd cadR fpk gyrA.